2000
DOI: 10.1007/s002100000262
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of inhibition by ethanol of NMDA and AMPA receptor channel functions in cultured rat cortical neurons

Abstract: The effect and mode of action of ethanol on N-methyl-D-aspartate (NMDA) and alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptors of rat cortical neurons in primary culture were compared by means of the patch-clamp technique. The maxima of the concentration-response curves for both NMDA and AMPA were markedly depressed by ethanol without an apparent shift of the curves to the right. Ethanol inhibited the effects of NMDA and AMPA concentration-dependently and equally well. Excitatory amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Acute ethanol also inhibits the function of AMPARs (Akinshola et al, 2001; Akinshola et al, 2003; Dildy-Mayfield and Harris, 1992; Moykkynen et al, 2003; Nieber et al, 1998; Wirkner et al, 2000) although with lower potency than NMDARs (Frye and Fincher, 2000; Lovinger, 1995; Lovinger et al, 1989). EtOH slightly alters AMPAR-mediated synaptic responses [the amplitude or time course of EPSCs] at most synapses due to increased receptor desensitization (Ariwodola et al, 2003; Lovinger et al, 1990; Moykkynen et al, 2003; Moykkynen et al, 2009), but see (Mameli et al, 2005; Nie et al, 1993; Roberto et al, 2004b; Zhu et al, 2007).…”
Section: 1 Glutamate and Etoh Effectsmentioning
confidence: 99%
“…Acute ethanol also inhibits the function of AMPARs (Akinshola et al, 2001; Akinshola et al, 2003; Dildy-Mayfield and Harris, 1992; Moykkynen et al, 2003; Nieber et al, 1998; Wirkner et al, 2000) although with lower potency than NMDARs (Frye and Fincher, 2000; Lovinger, 1995; Lovinger et al, 1989). EtOH slightly alters AMPAR-mediated synaptic responses [the amplitude or time course of EPSCs] at most synapses due to increased receptor desensitization (Ariwodola et al, 2003; Lovinger et al, 1990; Moykkynen et al, 2003; Moykkynen et al, 2009), but see (Mameli et al, 2005; Nie et al, 1993; Roberto et al, 2004b; Zhu et al, 2007).…”
Section: 1 Glutamate and Etoh Effectsmentioning
confidence: 99%
“…Moreover, the effects of ethanol consumption on NMDA- and mGlu-R as well as Homer (a glutamatergic receptor scaffolding protein) subunit expression in the extended amygdala and Acb core are also influenced by the length of ethanol-withdrawal (Obara et al, 2009 ). Intracellularly, ethanol inhibits, non-competitively, the NMDAR-mediated calcium influx in the cortex, Acb, amygdala, hippocampus, and VTA (Nie et al, 1994 ; Wirkner et al, 2000 ; Roberto et al, 2004 ; Stobbs et al, 2004 ; Zhu et al, 2007 ). Additionally, ethanol's effects on NMDA receptor activity are followed by phosphorylation and internalization of NR2 subunits (Suvarna et al, 2005 ).…”
Section: Glutamatergic Neurotransmission: Interactions With Alcoholmentioning
confidence: 99%
“…Low concentrations (5–50 mM) of alcohol also inhibit AMPAR function (Akinshola et al, 2001; Dildy-Mayfield and Harris, 1992, Moykkynen et al, 2003; Wirkner et al, 2000). Our lab has shown that acute alcohol (5–66 mM) decreases excitatory post-synaptic potentials (EPSPs) and currents (EPSCs) in the CeA, and that these effects are mediated by both NMDAR and non-NMDAR mechanisms (Roberto et al, 2004b).…”
Section: Excitatory (Glutamatergic) Transmission In Amygdala and Alcmentioning
confidence: 99%